Landform evolution in the Marine Plain region, Vestfold Hills, East Antarctica - Quilty, PG (Antarctic Science, 2006)
Landforms of Marine Plain in the Vestfold Hills contrast with those of most in the Vestfold Hills. They include consistent land surfaces at 40+ m and 25 m, characteristics controlled by orientation of rock features, and imprints of phases of glaciation, deglaciation and marine and freshwater inundation. The 40+ m surface is widespread in the Vestfold Hills and has been noted previously. The 25 m level was an earlier coastline, is more localized and marked by water rounded boulders; it serves to differentiate clearly between two terrains of different relief and erratic distribution. The Pliocene sedimentary rocks below the 25 m level have been dislocated, probably during an interval of glaciotectonism caused by northward movement of sediments under an ice load due to northern extension of the Srsdal Glacier or expansion of the East Antarctic Ice Sheet some time after the mid-Pliocene. Soil development is active. These features are accompanied by the normal aspects of a glaciated landscape such as glacial striations, sand wedges, erratics, and patterned ground. Wind has been important in transporting sand and developing honeycomb weathering on exposed rock faces. Antarctic Science Ltd.